2004
DOI: 10.1063/1.1821640
|View full text |Cite
|
Sign up to set email alerts
|

Stress effect on magnetoimpedance in amorphous wires at gigahertz frequencies and application to stress-tunable microwave composite materials

Abstract:  The effect of tensile stress on magnetoimpedance (MI) in CoMnSiB amorphous wires at microwave frequencies (0.53 GHz) is investigated both experimentally and theoretically. In the presence of the dc bias magnetic field of the order of the anisotropy field, the impedance shows very large and sensitive change when the wire is subjected to a tensile stress: 100% and 60% per 180 MPa for frequencies 500 MHz and 2.5 GHz, respectively. It is demonstrated that this behavior owes mainly to the directional change in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 25 publications
(35 reference statements)
1
43
1
Order By: Relevance
“…However, the theoretical and experimental analysis conducted in [4][5][6][7] has shown that eff  changes very little with both the external axial magnetic field ex H and anisotropy field K H for frequencies much higher than the ferromagnetic resonance, although preserving its relatively high values (in the range of tens). Therefore, the dependence of the magnetoimpedance on various external factors such as a dc magnetic field or stress (which changes K H ) will be entirely determined by the static magnetization angle  .…”
Section: Index Terms-magnetoimpedance Ferromagnetic Amorphous Wiresmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the theoretical and experimental analysis conducted in [4][5][6][7] has shown that eff  changes very little with both the external axial magnetic field ex H and anisotropy field K H for frequencies much higher than the ferromagnetic resonance, although preserving its relatively high values (in the range of tens). Therefore, the dependence of the magnetoimpedance on various external factors such as a dc magnetic field or stress (which changes K H ) will be entirely determined by the static magnetization angle  .…”
Section: Index Terms-magnetoimpedance Ferromagnetic Amorphous Wiresmentioning
confidence: 99%
“…This effect has been proposed to be used as a stress-sensing mechanism in the composite structures. [5,6] In this paper, we have investigated the MI effect in CoMnSiB glass-coated amorphous wires with thermally induced nearaxial anisotropy. This wire shows a dc magnetization process which is dependent on a tensile stress, changing from almost a rectangular loop without a stress to a linear one when a strong stress is applied.…”
Section: Index Terms-magnetoimpedance Ferromagnetic Amorphous Wiresmentioning
confidence: 99%
See 1 more Smart Citation
“…Since glass exerts some mechanical stress on the metallic wire, a change in the magnetic response is expected; other works have rather investigated the effect of external stress [9,10], as well as that of various annealing methods [11,12]. Consequently, it is of interest to finely tune the physical properties through the control of the thickness and nature of the glass sheath.…”
Section: Introductionmentioning
confidence: 99%
“…While the metallic core provides the magnetic behavior, the cover has a protective and stress-inducting function. Due to its tiny dimensions and its particular effects like Giant Magnetoimpedance (GMI), [8][9][10][11][12][13][14] bistability, 15 ferromagnetic resonance, 16 and magnetoelastic resonance, these materials have been considered as promising sensor elements. Furthermore, since the metallic core is covered by a biocompatible Pyrex shell, they are suitable for biological and medical applications.…”
mentioning
confidence: 99%